The Impact of Acceptance and Commitment Therapy and Cognitive-Behavioral Therapy on Enhancing Psychological Flexibility in Students with Phubbing - Nikvash, Lida; Moghtader Osmavandani, Leila; Akbari , Bahman; Haghparast, Tayebeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study investigated the impact of two therapeutic approaches—Acceptance and Commitment Therapy (ACT) and Cognitive-Behavioral Therapy (CBT)—on enhancing psychological flexibility in students suffering from phubbing. Methods and Materials: This study employed a quasi-experimental design with a pre-test, post-test, and a two-month follow-up phase. The study sample consisted of 45 students with phubbing behavior who were randomly assigned to three groups of 15: the ACT group, the CBT group, and the control group. The Psychological Flexibility Scale was used to collect data, and the results were analyzed using repeated measures analysis of covariance (ANCOVA) and Bonferroni post hoc tests. Findings: The results indicated that both ACT and CBT had a significant effect on improving psychological flexibility compared to the control group (F = 47.490, η = 0.698). Notably, at the follow-up stage, ACT showed superior performance compared to CBT. In a more detailed analysis of subscales, ACT outperformed CBT, especially during the follow-up period. Regarding the psychological flexibility variable, post hoc test results revealed that the ACT group demonstrated significantly greater improvement in the follow-up phase compared to the CBT group. Conclusion: Based on the findings of this study, it is recommended that ACT, as a long-term effective approach, be considered alongside CBT in university and educational center support and counseling programs to enhance psychological flexibility in students with phubbing behavior. These interventions may contribute to the enhancement of students’ psychological capabilities and the reduction of harm associated with phubbing.